Alcohol Induced Psychotic Disorder: a comparitive study in patients with alcohol dependance, schizophrenia and normal controls - Jordaan, Gerhard; Emsley, R. A. (Stellenbosch : University of Stellenbosch, 2010)
Thesis(DMed (Psychiatry))-- University of Stellenbosch, 2007.